Determinant of service utilization for triple elimination of mother-to-child transmission of HIV, syphilis, and hepatitis B among women living with HIV during COVID-19 pandemic in Indonesia - Ngakan Putu Anom Harjana; Sally Nita; Meirinda Sebayang; Oldri Sherli Mukuan; Asti Setiawati Widihastuti (DiscoverSys Inc., 2022)
Background: HIV-AIDS and sexually transmitted infections are still a public health burden in Indonesia. Women living with HIV have a higher risk of transmitting HIV, Syphilis, and Hepatitis B to their babies. While the effort to increase the services coverage for the prevention of mother-to-child transmission (PMTCT) was detained due to the COVID-19 pandemic and the lack of published studies that explore this, this study aimed to assess the determinant of service utilization for triple elimination of mother-to-child transmission of HIV, Syphilis, and Hepatitis B among women living with HIV during COVID-19 pandemic in Indonesia. Methods: This cross-sectional study targeted women living with HIV in Indonesia who are planning to get pregnant. A simplified-snowball sampling technique was used in this study. A dependent variable in this study was the service utilization of PMTCT for HIV, Syphilis, and Hepatitis B. In contrast, the independent variables in this study consisted of demographic characteristics, perception according to Health Belief Model constructs, and stigma and discrimination experiences. Multiple logistic regression was used to find the determinants of service utilization. Results: Among 336 women living with HIV that were interviewed, only 28.27% (95% CI = 23.69 – 33.34) accessed the PMTCT services during the COVID-19 pandemic. Moreover, the likelihood of PMTCT service utilization was decreased among the women living with HIV who perceived higher barriers (aOR = 0.56; 95% CI = 0.31 – 0.99) and experienced stigma and discrimination from partner (aOR = 0.50; 95% CI = 0.25 – 0.99). On the other hand, the PMTCT service utilization was increased among those who perceived less severity (aOR = 2.07; 95% CI = 1.21 – 3.54). No other factors were associated with the PMTCT service utilization among women living with HIV during the COVID-19 pandemic. Conclusion: The PMTCT service utilization was relatively low, increased by the higher perceived severity, and reduced among those who perceived higher barriers and experienced stigma and discrimination from the partner. Therefore, improving the knowledge about HIV, Syphilis, and Hepatitis B related to PMTCT services is essential, as well as providing social support to reduce the stigmas and discrimination among women living with HIV.